(untitled) (INNOTEC, 2018)
Water temperature is a fundamental parameter to understand the dynamics of continental waters. Surface water temperature trend and variability of the large reservoirs of the Río Negro river, Rincón del Bonete and Baygorria, using 16 years of satellite data (MUR-GHRSST) with a spatial resolution of 0.01º between 2002 and 2018 was studied. The average temperature was 18.8 ºC, with a minimum of 12.1 ºC and maximum of 25.2 ºC, in July and January, respectively. Spring and autumn showed the highest intraseasonal variability, and winter the highest interannual variability. The surface temperature of the reservoirs showed a signifcant trend towards warming of 1.3 °C per decade for spring-summer, while the seasons of autumn and winter did not exhibited a signifcant trend. The warming trend increased towards downstream. The satellite information was correlated with opportunistic observed data (n = 67), with a correlation of 0.94 and a root mean square error of 1.92 ºC. Generating time series of continuous measurements in situ would allow an evaluation of the product and viability for operational usage. These results demonstrate the utility of remote sensing of water temperature as a monitoring tool based on freely accessible information. In addition, the seasonal cycle, trend and variability of the reservoirs of the Río Negro river were described for the first time. It is expected that these results contribute to the environmental management measures of the Río Negro river reservoirs.